If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17 + 15 + 6X + -23 = 10 + -8X Reorder the terms: -17 + 15 + -23 + 6X = 10 + -8X Combine like terms: -17 + 15 = -2 -2 + -23 + 6X = 10 + -8X Combine like terms: -2 + -23 = -25 -25 + 6X = 10 + -8X Solving -25 + 6X = 10 + -8X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '8X' to each side of the equation. -25 + 6X + 8X = 10 + -8X + 8X Combine like terms: 6X + 8X = 14X -25 + 14X = 10 + -8X + 8X Combine like terms: -8X + 8X = 0 -25 + 14X = 10 + 0 -25 + 14X = 10 Add '25' to each side of the equation. -25 + 25 + 14X = 10 + 25 Combine like terms: -25 + 25 = 0 0 + 14X = 10 + 25 14X = 10 + 25 Combine like terms: 10 + 25 = 35 14X = 35 Divide each side by '14'. X = 2.5 Simplifying X = 2.5
| 2+6(5x+3)=12 | | in(2x)=5.5 | | (-3w^4/v^2)^2 | | -4m=38 | | 2x+1.2=8.8 | | X+X=19 | | =(4i-j)xj | | 16y+8x+6=180 | | 8x+7z=5+7y | | 5n=-17 | | n-9.32=16.2 | | 7a+15=4a+38 | | .25(n)=7n+5 | | z-18.03=-14 | | 5(2x-8)-5=5(x-3)-5 | | 16+3s-2s=24+24-20 | | 5-8(4x-4)=-7 | | 3(x+2)=6(x-1)+6 | | -16=y-13 | | 60-.04x=80 | | 3/10-(-2/3) | | -3=z-18 | | 30+3*x-2*(12-x)=38 | | 10-2m=m+4 | | 8y-7=14y+23 | | 4x+12=38 | | -6x^2=-35 | | 10/62 | | 9x-7=6x+38 | | 50=x-15 | | 27x+901= | | 8x-3=5x-57 |